THU0587 Public awareness of rheumatic diseases in cyprus - need for improvement. (15th June 2017) - Joseph, J; Armata, I; Antoniadou, A; Maini, P
Abstract : Background: Public awareness regarding rheumatic diseases is a constant aim of patient societies and health care professionals in rheumatology. A high level of awareness will help identification and early treatment, it would avoid unnecessary investigations and costs and more importantly, it would assist functioning of patients with such conditions in society, with the understanding and support they deserve. Objectives: The aim was to study public awareness regarding rheumatic conditions. Specifically, what constitutes a rheumatic condition, which doctor deals with these, what is their frequency and what age groups are affected. Methods: During the rheumatic diseases awareness week in May 2016, doctors, medical students and members of the Cyprus League against Rheumatism, walked the streets of major cities and invited passers-by to answer a few simple questions. This was optional and at the end of the questions, information was provided, based on the answers and on any additional queries raised by people. Results: 400 people provided answers. There were slightly more women than men and ages ranged from 13 to 86 years. Almost 50% did not know what a rheumatologist does. Only 11% could name 3 rheumatic conditions. Although the majority stated that rheumatic diseases occur in the elderly, 2/3 were unaware that they can affect children. Most people correctly identified which specialists should deal with asthma or eczema, but a huge majority did not know who should be consulted for back pain, tendon problems or osteoporosis. Although 75% had heard of rheumatoid and osteoarthritis, 75% of people had never heard of ankylosing spondylitis or fibromyalgia and only about half had heard of psoriatic arthritis or lupus. Most people stated that rheumatic conditions in general, affect 10–20% of people. Conclusions: There was significant lack of awareness as to what rheumatologists do, what constitutes a rheumatic disease, the fact that it affects young people and the link between rheumatology and back pain, tendon problems and osteoporosis. All these points need to be included in public education. Of the major rheumatic diseases, the next awareness campaign needs to include ankylosing spondylitis, fibromyalgia, psoriatic arthritis and lupus. Disclosure of Interest: None declared